Transcriptome Analysis of Cryphonectria parasitica Infected With Cryphonectria hypovirus 1 (CHV1) Reveals Distinct Genes Related to Fungal Metabolites, Virulence, Antiviral RNA-Silencing, and Their Regulation - Chun, Jeesun; Ko, Yo-Han; Kim, Dae-Hyuk (Frontiers in Microbiology, 2020)
Comprehensive transcriptome analysis was conducted to elucidate the molecular basis of the interaction between chestnut blight fungus, Cryphonectria parasitica, and single-stranded RNA (ssRNA) mycovirus Cryphonectria hypovirus 1 (CHV1), using RNA-sequencing (RNA-seq). A total of 1,023 differentially expressed genes (DEGs) were affected by CHV1 infection, of which 753 DEGs were upregulated and 270 DEGs were downregulated. Significant correlations in qRT-PCR analysis of 20 randomly selected DEGs and agreement with previously characterized marker genes validated our RNA-seq analysis as representing global transcriptional profiling of virus-free and -infected isogenic strains of C. parasitica. Gene Ontology analysis of DEGs indicated that “cellular aromatic compound metabolic process” and “transport” were the two most enriched components in the “biological process”. In addition, “cytoplasm” was the most enriched term in the “cellular component” and “nucleotide binding” and “cation binding” were the two most enriched terms in the “molecular function” category. These results suggested that altered expression of genes encoding numerous intracellular proteins due to hypoviral infection resulted in changes in specific metabolic processes as well as transport processes. Kyoto Encyclopedia of Genes and Genomes function analysis demonstrated that pathways for “biosynthesis of other secondary metabolites”, “amino acid metabolism”, “carbohydrate metabolism”, and “translation” were enriched among the DEGs in C. parasitica. These results demonstrate that hypoviral infection resulted in massive but specific changes in primary and secondary metabolism, of which antiviral fungal metabolites were highly induced. The results of this study provide further insights into the mechanism of fungal gene regulation by CHV1 at the transcriptome level.